Studies on Physico-chemical Characteristics of Lentic and Lotic Water Bodies of River Mahananda at Jhaua, Katihar (Bihar) - Deo Jha, Krishna; Jha, N.N.; Kumar, A.; Yadav, J.K. (Asian Journal of Chemistry, 2016)
This paper is an attempt to investigate the pollution level of the river Mahananda at Jhaua for some physico-chemical parameters like temperature, pH, alkalinity, heavy metals, total hardness, etc. The results show significant variation in these parameters but the pollutional level of the water is minimum at Jhaua.